UNDERSTANDING THE CULTURAL DIMENSION OF DISPLACEMENT: A SCIENTOMETRIC ANALYSIS - Pattanaik, Yashodhara; Mohanty, Dr. Madhubrata; Pati, Dr. Jayadev (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Culture is the most sensitive yet important thread that links us to our past. It gives communities an identity and helps with the continuity of the working of society. It is a big part of us and is rooted in the way the society functions which reflects the collective experience and memory of the people. In this study, we have presented a bibliometric analysis of intellectual works derived from Scopus database that discusses the cultural aspect of displacement. Using R Studio and VOS viewer we were able to examine the productions, citations, sources, themes, contributors, affiliations, collaborations and network. Also, a literature review of the most cited documents is also presented, the list of which was drawn from the bibliometric analysis. The findings present a significant growth in the number of scientific production in the last ten years (2016- 2025) while the citations remain low. The thematic mapping reveals that the cultural aspect of displacement is discussed through active engagement in interdisciplinary works where topics like gentrification and refugee have emerged as highly engaging themes. Collaboration patterns are limited to USA, UK, Australia and few European countries. The analysis also shows limited contributions from authors and affiliations. The results present a strong need to integrate culture as a core theme in displacement related studies and a need for thematic and geographically diverse approach in the production of research work relating to the cultural aspect of displacement.